Lumbosacral Epidural Anaesthesia in a Dog and its Complication – A Case Report - Tomáš Lipták; Jakub Fuchs; Nikolay Kozlov; Sergey Pozyabin; Bishal Bhattarai; Mária Kuricová (The Indian Veterinary Journal, 2023)
In this report, we present a rarely described case of anaesthetic complication in a 2-year-old intact female Shih Tzu, including clinical findings, magnetic resonance imaging results, and outcome. The dog was admitted to the hospital with paraplegia and lumbosacral pain, which we attributed to iatrogenic trauma resulting from epidural injection and accidental dural sac puncture.